Satisfaction levels of patients attending the outpatient department of a tertiary care center of India - Kumar, Vijay; Biswas, Ratnadeep; Ojha, Vishnu S.; Kaushal, Kishore (Publishing Office of the University of Rzeszow, 2023)
Introduction and aim. Any hospital’s outpatient department (OPD) is regarded as the storefront of the facility, and patient satisfaction is an important measure of healthcare quality. Hence, this cross-sectional study was conducted in different OPDs at a tertiary care center. Material and methods. Two hundred patients were recruited, and structured personal interviews were conducted with questions based on the Patient Satisfaction Questionnaire Short Form (PSQ-18). T-tests and analysis of variance (ANOVA) were used to compare satisfaction scores between variables. Results. Upon analysis, 86% of the patients rated their overall experience as either ‘very good’ or ‘good’. Interpersonal manners (mean score±SD; 4.60±0.55), communication (4.39±0.66), general satisfaction (4.03±0.79), and technical qualities (3.86±0.57) were the domains in which the patients were most satisfied, while time spent with the doctor (3.77±0.89), accessibility and convenience (3.77±0.67), and financial aspects (3.37±0.83) were the areas that lagged. Conclusion. Satisfaction scores were found to vary significantly with gender, age, waiting times, and the number of visits per day. Regular patient satisfaction surveys should be conducted in all hospitals for devising interventions to provide patients with the best possible care.
Approval was taken from the institute’s ethics committee of Patna Medical College (IEC/PMC/624/2022). The study was conducted in accordance with the Declaration of Helsinki after taking consent from all the participants.
Keywords: health care quality; patient care; patient satisfaction; PSQ-18; quality improvement research